‘The meaning of my life will always be to defend our Motherland’: Raising and educating citizens in a child protection institution in Mexico (Journal of Comparative Social Work, 2019)
EnglishThe point of departure of this paper is that childhood is socially constructed and continuously re-defined through public policies, laws, practices and ideologies. The paper explores the perspectives on children, upbringing and socialization as reflected in the manuals, forms and questionnaires of social workers in a child protection institution in Mexico. It employs a theoretical lens borrowed from Childhood Studies, using three dominant images of childhood—the Dionysian, Apollonian and Athenian—to examine the links between discursive constructions of childhood and ways of governing institutionalized children. Four overarching themes were identified as representative of predominant concepts of values concerning children and child rearing in an institutionalized context in the documents: (1) Patriotism, (2) Work ethics, (3) Hygiene, and (4) Physical experiences and sexuality. The analysis reveals how children are perceived primarily as future citizens, with their upbringing being a part of a wider nation-building project. Hence, there is an emphasis on how to become a ‘decent’ labourer, internalize the values of- and loyalty to the nation-state, and develop into a ‘moral’ and ‘civilized’ citizen. It is argued that institutional socialization is part and parcel of a political ideology that reinforces the idea of children as relatively passive socialization objects.Spanish"El sentido de mi vida siempre será defender nuestra patria”: Criando y educando ciudadanos en instituciones de protección infantil en México. El punto de partida de este artículo es que la infancia es construida socialmente, y que es continuamente redefinida a través de las políticas públicas, las leyes, las prácticas y las ideologías. Este artículo explora las perspectivas sobre los niños, la crianza, y la socialización según se reflejan en los manuales, planillas y cuestionarios de los trabajadores sociales en una institución de protección infantil en México. Se emplea la propuesta teórica tomada de los Estudios de la Infancia, usando tres imágenes dominantes (Dionisíaca, Apolínea y Ateniense) para examinar los vínculos entre las construcciones discursivas sobre la infancia y las formas que gobiernan a los niños institucionalizados. Se identificaron cuatro temas relevantes como representativos de los conceptos de valores predominantes en los documentos respecto a los niños,  y cuidado infantil en un contexto institucionalizado: (1) Patriotismo, (2) Ética de trabajo, (3) Higiene, y (4) Experiencias físicas y sexualidad. El análisis revela cómo los niños son percibidos primeramente como futuros ciudadanos, y su crianza es parte de un proyecto más amplio de construcción de la nación. De este modo hay un énfasis en cómo convertirse en un trabajador “decente”, internalizar los valores de y la lealtad al Estado nación, y desarrollar un ciudadano moral y civilizado. Se afirma que la socialización institucional es parte de la ideología política que refuerza la idea de los niños como objetos de socialización relativamente pasivos.